(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The financial authorities can use this for evaluating their performance in future, which will help to analyses financial statements and help to apply the resources of the company properly for the development of the company and TT employees to bring overall growth. The print media industry in India is more than a century old. Also it is a well- established industry. This industry mainly comprises of publishing newspapers and magazines. India has the second largest population and one of the fastest growing economies in the world. Along with these the increasing level of income of peoples and the robust competition in this industry help print media in its growth. Producers are increasing day by day, new entrants from outside India is also a factor of tough competition.